2016
DOI: 10.3390/ijms17071058
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing Analyses between the Cytoplasmic Male Sterile Line and Its Maintainer Line in Welsh Onion (Allium fistulosum L.)

Abstract: Cytoplasmic male sterility (CMS) is important for exploiting heterosis in crop plants and also serves as a model for investigating nuclear–cytoplasmic interaction. The molecular mechanism of cytoplasmic male sterility and fertility restoration was investigated in several important economic crops but remains poorly understood in the Welsh onion. Therefore, we compared the differences between the CMS line 64-2 and its maintainer line 64-1 using transcriptome sequencing with the aim of determining critical genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…It suggests that mitochondrial respiratory related enzymes play a vital role in the eggplant MS line. The result is consistent with a previous study [ 41 ], in which the CMS related genes was explored in MS line of welsh onion. As we know, MS of many plants were associated with mitochondria, especially the CMS.…”
Section: Discussionsupporting
confidence: 93%
“…It suggests that mitochondrial respiratory related enzymes play a vital role in the eggplant MS line. The result is consistent with a previous study [ 41 ], in which the CMS related genes was explored in MS line of welsh onion. As we know, MS of many plants were associated with mitochondria, especially the CMS.…”
Section: Discussionsupporting
confidence: 93%
“…Ethylene-responsive transcription factor 115 and transcriptional factor basic helix-loop-helix 137 were both significantly upregulated in ogu CMS abortive buds. Therefore, our results were basically consistent with the results of previous studies [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], and the genes discovered related to energy metabolism, oxidation reduction process and phenylpropanoid biosynthesis, ethylene-responsive transcription factor 115 and transcriptional factor basic helix-loop-helix 137 may be important factors contributing to Broccoli ogu CMS pollen abortion and bud abortion. Further experiments are needed to elucidate the molecular mechanisms of these genes that lead to broccoli CMS and bud abortion.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that the genes involved in reactive oxygen species (ROS) homeostasis or antioxidative system balance may be important factors contributing to pollen abortion in cotton [ 46 ] and wheat [ 47 ]. Carbohydrate and energy metabolisms, oxidation-reduction system and phenylpropanoid metabolism pathways related genes may be important factor for CMS in soybean [ 48 ], rapeseed [ 49 ], cabbage [ 50 ], onion [ 51 ] and wheat [ 52 ]. Male sterility might be related to energy metabolism turbulence, excessive ethylene synthesis, and suffocation of starch synthesis in pepper [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…CMS is caused by mitochondrial genes coupled with nuclear genes [ 7 ] and is considered a complicated biological process that involves many metabolic pathways. Therefore, comparative transcriptome analyses have been extensively used to study the molecular mechanisms of CMS in plants, including the kenaf CMS line P3A [ 8 ], soybean CMS line NJCMS1A [ 9 ], Welsh onion CMS line 64-2 [ 10 ], and cabbage CMS line PM [ 4 ].…”
Section: Introductionmentioning
confidence: 99%